Framing ATM Cells for Satellite Onboard Switching - Alzate Monroy, Marco Aurelio (Ingeniería, 2000)
In this paper we analyze a simple model to study the convenience of grouping ATM cells into frames before transmission over satellite channels for onboard switching. We consider a switch where the input/output ports are mapped to the spot beams of the satellite, with several Bernoulli users within each spot beam. We obtain exact results for the delay in the terrestrial multiplexing system, based on the grouping of states of a Markov chain into equivalent cost classes. Then we obtain an approximate solution for the onboard switch delay, based on a search algorithm of the most probable states in an infinitesate Markov chain. By using this kind of framing we reduce the number of switching operation per unit time, so we can use smaller and lighter onboard switches. However, although we also reduce the contention for accessing the uplink channel, this reduction cannot always compensate for the additional delay we incur during the framing process.